2020
DOI: 10.1002/anie.202010981
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Tagging of Protein Lipoylation

Abstract: Protein lipoylation is a post‐translational modification of emerging importance in both prokaryotes and eukaryotes. However, labeling and large‐scale profiling of protein lipoylation remain challenging. Here, we report the development of iLCL (iodoacetamide‐assisted lipoate‐cyclooctyne ligation), a chemoselective reaction that enables chemical tagging of protein lipoylation. We demonstrate that the cyclic disulfide of lipoamide but not linear disulfides can selectively react with iodoacetamide to produce sulfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 32 publications
0
25
0
9
Order By: Relevance
“…These ‘relatively minor modifications’ were generally regarded as constitutive and inert marks in histones ( 4 ), until the discovery of GCN5 as the first histone acetyltransferase (HAT) from Tetrahymena thermophile , a ciliated protozoan, by C. David Allis and James E. Brownell in 1996 ( 5 , 6 ). Later, it was demonstrated that the lysine residue is particularly active and can be regulated by a variety of PLMs, including acylation modifications such as acetylation ( 7 ), crotonylation ( 8 ), succinylation ( 9 ) and lactylation ( 10 ), ubiquitin and ubiquitin-like (Ub/Ubl) conjugations such as ubiquitination ( 11 ) and sumoylation ( 12 ), and other types of PLMs such as methylation ( 13 ) and lipoylation ( 14 ). PLMs occurred at histone lysine residues constitute the ‘histone code’ together with other histone modifications, and play a critical role in transcriptional regulation and gene expression ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…These ‘relatively minor modifications’ were generally regarded as constitutive and inert marks in histones ( 4 ), until the discovery of GCN5 as the first histone acetyltransferase (HAT) from Tetrahymena thermophile , a ciliated protozoan, by C. David Allis and James E. Brownell in 1996 ( 5 , 6 ). Later, it was demonstrated that the lysine residue is particularly active and can be regulated by a variety of PLMs, including acylation modifications such as acetylation ( 7 ), crotonylation ( 8 ), succinylation ( 9 ) and lactylation ( 10 ), ubiquitin and ubiquitin-like (Ub/Ubl) conjugations such as ubiquitination ( 11 ) and sumoylation ( 12 ), and other types of PLMs such as methylation ( 13 ) and lipoylation ( 14 ). PLMs occurred at histone lysine residues constitute the ‘histone code’ together with other histone modifications, and play a critical role in transcriptional regulation and gene expression ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, proteomic profiling of lipoylation has also been performed by functionalising lipoamide in situ, utilising the reactivity of the lipoamide 1,2-dithiolane ring to chemoselectively conjugate cyclooctyne probes to lipoamide-bound proteins in bacterial and mammalian lysates. [52] The minimalist photocrosslinker was also exploited in the recently developed ATP mimetic 2.10, which was found to enrich 59 known ATP-binding proteins in A549 cell membrane fractions, as well as highly abundant cytosolic ATP binders from cell lysates. [53] A contrasting chemical proteomics method, thermal proteome profiling (TPP), [54] which examines the stabilisation of proteins induced by ligand binding, has also been recently used to profile ATPbinding proteins, finding 315 of 7859 of proteins annotated with GO terms relating to this cofactor.…”
Section: Cofactor Interactome Discovery Using Photoaffinity-functiona...mentioning
confidence: 99%
“…Diese Sonde wurde in Proteomik‐Experimenten verwendet, wobei eine neue Delipoylierungsfunktion von Sirt2 aufgedeckt wurde. Kürzlich wurde das Proteom‐Profiling der Lipoylierung auch durch die Funktionalisierung von Liponamid in situ durchgeführt, wobei die Reaktivität des 1,2‐Dithiolan‐Rings des Liponamids genutzt wurde, um chemoselektiv Cyclooctin‐Sonden an Liponamid‐gebundene Proteine in bakteriellen und Säugetier‐Lysaten zu konjugieren [52] …”
Section: Untersuchung Von Cofaktor‐interaktomen Mithilfe Funktionalis...unclassified